1977
DOI: 10.1136/bmj.1.6059.488
|View full text |Cite
|
Sign up to set email alerts
|

Effect of eating liquorice on the renin-angiotensin aldosterone axis in normal subjects.

Abstract: SummaryThe effect of confectionery liquorice on electrolyte status and the renin-angiotensin-aldosterone (RAA) axis was studied in 14 healthy volunteers. They ate liquorice in daily doses of 100 g or 200 g (equivalent to 0 7-14 g glycyrrhizinic acid) for one to four weeks.Plasma potassium concentrations fell by over 03 mmol/l in 11 people, including four who had to be withdrawn from the study because of hypokalaemia. One or more values of the RAA axis, especially plasma renin activity and urinary aldosterone c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(38 citation statements)
references
References 2 publications
2
36
0
Order By: Relevance
“…Serum potassium concentrations fell by more than 0.3 mmol/L in 11 people, including four who had to be withdrawn from the study due to marked hypokalemia (4). These findings will not surprise senior physicians, who may recall episodes of serious potassium loss secondary to carbenoxolone, which is a liquorice-containing medication used within the past 20 years for the treatment of gastric ulceration.…”
Section: Discussionmentioning
confidence: 81%
“…Serum potassium concentrations fell by more than 0.3 mmol/L in 11 people, including four who had to be withdrawn from the study due to marked hypokalemia (4). These findings will not surprise senior physicians, who may recall episodes of serious potassium loss secondary to carbenoxolone, which is a liquorice-containing medication used within the past 20 years for the treatment of gastric ulceration.…”
Section: Discussionmentioning
confidence: 81%
“…Treatment with SNMC is not without side effects, which are seen in a minority of patients; the main side effects are hypertension, sodium and fluid retention, worsening ascites, and hypokalemia (44,45). Glycyrrhizin should be used cautiously in patients with a history of hypertension or renal failure or currently using cardiac glycosides.…”
Section: Glycyrrhizin (Licorice Root Extract)mentioning
confidence: 98%
“…In addition, the development of pseudoaldosteronism, characterized by sodium retention, exaggerated potassium excretion, and suppression of both renin and aldosterone was described in patients who took large amounts of licorice or glycyrrhizin for long periods [1,[6][7][8][9]. However, the alterations in blood pressure and electrolyte balance in patients taking licorice or glycyrrhizin were quantitatively variable, with some individuals showing little or no change, whereas others exhibited gross abnormalities [10,11]. The present study demonstrated two points in patients with chronic hepatitis treated with 546mg of glycyrrhizin.…”
Section: Introductionmentioning
confidence: 99%